(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study explores the factors motivating small business owners to adopt social media marketing, focusing on key drivers such as cost-effectiveness, customer engagement, and brand visibility. A quantitative research approach was used, collecting data from 100 small business owners through a structured questionnaire. The findings reveal that cost effectiveness is the primary motivation, cited by 78% of respondents, followed by enhanced customer interaction and increased brand visibility. Platforms like WhatsApp, Instagram, and Facebook are preferred for their unique strengths in communication and marketing. However, challenges such as limited technical skills, time constraints, and difficulties in measuring return on investment (ROI) were significant barriers to effective adoption. The study provides insights that can help small businesses better leverage social media platforms for sustained growth and competitiveness in the digital marketplace.